Immediate Outcome of Intrauterine Growth Restricted Infants (Sir Salimullah Medical College Journal, 2023)
Background: Intrauterine growth restriction (IUGR) is one of the major public health issues in developing countries like Bangladesh. IUGR has got significant importance due to its approach towards post neonatal, infant and childhood mortality and morbidity.Objective: To identify immediate outcome of IUGR infants.Methods: This case control study was conducted in department of Neonatology at BSMMU, Dhaka from August 2015 to July 2016, where 98 newborns in the NICU during study period were the study population. All the IUGR babies were labeled as case (Group- A), n=49 and the babies of the same gestational age were labeled as control (Group-B), n=49. The outcome was observed by the caution and careful NICU follow up of the baby. After collection, data were entered into a personal computer and were edited, analyzed, plotted in graphs and tables. Data were analyzed by chi square test, Mann Whitney U tests, using the statistical package for social sciences (SPSS) version 20. P values less than 0.05 (95% CI) were considered statistically significant.Result: During the study in case group, hypoglycemia (p=0.007) & hyperbilirubinemia (P=